Grammatical Prohibitions In The Transitivity Of Verbs According To Al-Rummani: A Study Of What Is Not Permissible In His Commentary On Sibawayh’s Book/ المحظورات النَّحويَّة في تعدِّي الأفعال عند الرُّمَّانيّ: دراسة في ما لا يجوز في شرحه لكتاب سيبويه - Halima Talib Jumaa; Wissam Najm Abdullah (Ijaz Arabi Journal of Arabic Learning, 2026)
This study seeks to examine and analyze Al-Rummani’s grammatical positions in "What is Impermissible", with a particular focus on issues related to the transitions that arise from them. The aim of the research is to identify the nature of the prohibitions established by Al-Rummani, clarify their grammatical rationales, and compare them with the views of Sibawayh and other grammarians. This study adopted the analytical deductive method, extracting Al-Rummani’s texts related to the transitivity of verbs in the chapter (what is not permissible), then analyzing their grammatical structure and the reasons that Al-Rummani used as evidence, while comparing them with the opinions of grammarians who preceded and followed him. The study concludes that al-Rummani expanded substantially in presenting and analyzing the various forms of prohibitions related to verbal transitivity, grounding them in logical and semantic arguments. Meaning, for Al-Rummani, was a fundamental pillar that led him to judge certain grammatical constructions as impermissible due to semantic corruption. Al-Rummani was not merely a commentator on Sibawayh’s Kitab; rather, he exercised analytical judgment in his grammatical prohibitions in Ma La Yajuz provides evidence of the development of grammatical thought and the multiplicity of its justificatory and analytical pathways. Notably, this study highlights the grammatical prohibitions identified by Al-Rummani in Ma La Yajuz, affirming the possibility of employing these prohibitions to enhance the teaching of the boundaries of Arabic grammar to non-native speakers and to develop their awareness of the Arabic grammatical system.